Impact of Multiple Intelligences and Problem-Based Learning on Mathematical Literacy and Self-Efficacy in Junior High School Students - Dina Damiyanti Hidayat; Ali Mahmudi (STAI Hubbulwathan Duri, 2025)
Mathematical literacy and self-efficacy are essential skills that influence students' success in mathematics. This study examines the impact of multiple intelligence-based and problem-based mathematics learning on students' mathematical literacy and self-efficacy. Additionally, it investigates whether multiple intelligence and problem-based learning are more effective than scientific learning approaches in improving these competencies. This quasi-experimental study employed a one-group pretest-posttest design. The study was conducted at State Junior High School 3 Yogyakarta during the even semester of the 2023/2024 academic year. The sample consisted of 64 students from two eighth-grade classes (VIII F and VIII E, each with 32 students). Data were collected using questionnaires to assess multiple intelligences before learning, observations to monitor learning implementation, and pretest-posttest assessments and questionnaires to evaluate students' progress. Data were analyzed using Multivariate Analysis of Variance (MANOVA) with Hotteling’s T² test and Independent Sample T-test statistics. Findings indicate that multiple intelligence-based mathematics learning using problem-based and scientific approaches significantly influences students' mathematical literacy and self-efficacy. Additionally, problem-based learning was found to be more effective than scientific learning, as it resulted in higher improvements in students' mathematical literacy and self-efficacy scores. The study concludes that integrating multiple intelligence with problem-based mathematics learning positively impacts students' mathematical literacy and self-efficacy. Future research should explore long-term effects and broader student populations to further validate these findings.